Optimizing Tuberose (Polianthes tuberosa L.) Production Using Mycorrhiza and Biostimulants to Enhance Water-Deficit Tolerance - Mahdyeh Saravani; Abdolrahman Rahimian Boogar; Mehdi Aran; Dariush Ramezan; Meisam Zargar; Simbo Diakite (Horticulturae)
A water deficit can significantly limit the sustainable production of plants, resulting in reduced growth, development, and flowering. The use of biostimulants improves plant stability and promotes growth under low-irrigation conditions. This study evaluated the effects of biostimulators on the growth, development, and flowering of tuberose (Polianthes tuberosa L.) under water-deficit conditions. This experiment was conducted using a completely randomized design with three replications in pots and eight treatments: four irrigation regimes (100%, 80%, 60%, and 40%), and four biostimulant treatments (foliar application of seaweed extract (SE) at concentrations of 500, 1000, and 2000 ppm; humic acid (HA) application at concentrations of 150, 300, and 600 ppm; inoculation of the bed with mycorrhiza; a control treatment without biostimulators). We measured the length, diameter, and fresh and dry weight of the flower pedicel; the number of leaves per plant; the fresh and dry weight of the leaves, stem, and root of each plant; and the content of photosynthetic pigments, phenol, proline, carbohydrates, and flavonoids. The results of this study showed that the growth and development of tuberoses were positively affected by different irrigation levels and biostimulants. The highest morphological characteristics were observed in plants irrigated at 100% field capacity. In contrast, the irrigation regime treatment of 40% of the field capacity combined with 600 mg/l of HA had the most detrimental effect on plant growth indicators. Findings suggest that application of 2000 ppm of SE biostimulant contributes to the mitigation of the negative effects of water deficit in tuberose production under greenhouse conditions as an irrigation water conservation strategy that can be exploited to maintain high yields.